Insect control : biological and synthetic agents - Gilbert, Lawrence I. [ (Lawrence Irwin)] , 1929-; Gill, Sarjeet S. (Elsevier ; Academic Press, 2010)
One of the most popular areas in entomology is control. This title includes articles covering insect growth- and development-disrupting insecticides, mechanisms and use of Bacillus thuringiensis, biology and genomics of polydnaviruses, and pheromones: function and use in insect control